(untitled) (Hoboken, N.J., 2005)
Each chapter of this contributed work has been authored by a recognized expert. This is an excellent textbook for graduate and advanced undergraduate students in electrical engineering, computer engineering, and computer science, as well as a must-have reference that will help engineers, programmers, and technologists develop systems that are secure and reliable.
Keywords: Fault-tolerant computing,Fault-tolerant computing,Computers,Khả năng chịu đựng lỗi máy tính,Khả năng chịu đựng lỗi máy tính,Máy tính; Reliability,Độ tin cậy